Students’ perceptions with different CEFR levels on foreign teachers using L1 in EFL instruction - Kiki Juli Anggoro; Ahn Nguyet Nguyen (Universitas Syiah Kuala, 2021)
The demand for foreign teachers of English as a Foreign Language (EFL) has been high in non-English speaking countries, including Thailand. As foreigners have resided in the country for several years, they picked up students’ first language (L1) competence. Several foreign teachers, to some extent, utilized this mastery of L1 to assist the English instruction. This research aimed to explore how students with different Common European Framework of Reference for Languages (CEFR) levels perceive foreign English teachers’ use of L1. Three hundred twenty students from Walailak University participated in the survey. A quantitative survey and qualitative interview were used to collect data. Descriptive and inferential statistics were performed to analyze quantitative data, while content analysis was administered to investigate the qualitative data. The quantitative findings revealed a significant difference in students’ perceptions, Welch’s F(2,68.42)=11.304, p .05. The qualitative findings exposed that students in level A1 had significantly different perceptions compared to those in levels A2 and B1. Students who supported L1 integration disclosed that it ameliorated communication, enhanced learning motivation, and improved academic achievement. Additionally, students who opposed L1 expressed that English’s full usage developed their learning motivation and academic accomplishment.